Is couching rare in the pediatric age group? a report of bilateral couching in a child (2019)
Background: Couching, an ancient procedure for cataract surgery, is unfortunately still being practiced in many developing countries. There are several reports of couching in adult populations; however, literature is sparse on its occurrence in children. Case report: We report a case of a 10-year-old boy who had bilateral couching on account of congenital cataracts due to presumed congenital rubella syndrome. The patient had initially presented to our clinic during neonatal period and was scheduled for surgery. Unfortunately, surgery was not performed due to various reasons which were either patient related or health system related. He represented to the eye clinic 6 years post-couching with complaints of poor vision. Conclusion: This report aims to highlight the fact that couching is, indeed, being performed on children’s eyes, especially as a consequence of inefficiencies in the eye healthcare delivery system.